Polymer, isolating membrane, pole piece, battery and electric device
Patent Information
- Application Number
- CN202380067058.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-07
- Filing Date
- 2023-11-17
- Publication Date
- 2025-04-25
AI Technical Summary
During the cycle process of existing batteries, the bonding force between the pole piece and the separator film is too strong, which leads to demolding and reduces the cycle performance of the battery. In addition, the hot pressing process has problems such as high cost and unstable bonding force.
A polymer including first and second organic polymers is used and prepared through emulsion polymerization technology. The polymer has no adhesive property at a certain temperature, is suitable for winding and unwinding of the isolation film, and has the properties of cold pressing process. Better adhesion ensures the tight fit between the pole piece and the isolation film.
It improves the cycle performance of the battery, enhances the cold-pressing adhesion between the isolation film and the pole piece, extends the service life of the battery, and reduces the production cost.
Smart Images

Figure CN119895009A_ABST
Abstract
Description
Polymers, separators, electrodes, batteries and electrical devices Technical Field
[0001] The present application belongs to the field of batteries, and specifically relates to a polymer, an isolation membrane, an electrode, a battery and an electrical device. Background Art
[0002] In recent years, with the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries has also continued to grow. Among them, the electrochemical performance of batteries has also attracted more and more attention.
[0003] Currently, the separator adhesive in batteries uses polyvinylidene fluoride. Polyvinylidene fluoride is coated on the separator, which is then wound with the electrode and then heated and pressed to bond the electrode to the separator, increasing the hardness of the battery cell and maintaining the consistency of the battery cell thickness. Without a hot pressing process, there will be a gap between the separator and the electrode, causing the battery cell to have openings, soft cells, etc., and the separator will also have wrinkles. However, after hot pressing, the adhesion between the electrode and the separator is too strong, causing the positive electrode and / or negative electrode to be easily demolded during the battery cycle, thereby reducing the battery's cycle performance.
[0004] Summary of the Invention
[0005] In view of the technical problems existing in the background technology, the present application provides a polymer, which aims to achieve cold pressing bonding between the isolation membrane and the electrode, thereby improving the cycle performance of the battery.
[0006] To achieve the above objectives, the present application provides a polymer in one aspect, comprising: a first organic polymer and a second organic polymer, wherein monomers of the first organic polymer include a first polymerized monomer, a second polymerized monomer, and a third polymerized monomer, and monomers of the second organic polymer include the first polymerized monomer, the third polymerized monomer, and a fourth polymerized monomer, and wherein the structure of the first polymerized monomer comprises:
[0007] wherein R1 comprises a hydrogen atom or an alkyl group of 1 to 18 carbon atoms, and R2 comprises an alkyl group of 1 to 18 carbon atoms,
[0008] The structure of the second polymerizable monomer comprises:
[0009] wherein R3 comprises a hydrogen atom, a substituted or unsubstituted alkyl group of 1 to 18 carbon atoms;
[0010] The structure of the third polymerizable monomer comprises:
[0011] wherein R4 comprises a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 comprises a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms;
[0012] The structure of the fourth polymerized monomer comprises:
[0013] Wherein, R6 includes a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0014] The present application includes at least the following beneficial effects: When the polymer of the present application is used in a separator, the polymer has no adhesive properties at a certain temperature, facilitating the winding and unwinding of the separator. However, after being wound with the positive and negative electrode sheets and then subjected to a cold pressing process, the polymer exhibits excellent adhesion, allowing the positive and negative electrode sheets to adhere tightly to the separator. Therefore, when the polymer of the present application is used in a separator, cold pressing bonding between the separator and the electrode sheet can be achieved, and the adhesion between the electrode sheet and the separator is suitable, thereby improving the cycle performance of the battery.
[0015] In some embodiments of the present application, the mass ratio of the first organic polymer to the second organic polymer is 1:(0.1-10), and can optionally be 1:(0.5-3). Therefore, when this polymer is used in a separator, it not only facilitates winding and unwinding of the separator, but also improves the cold-pressed bonding strength between the separator and the positive and negative electrode sheets, thereby enhancing the cycle performance of the battery.
[0016] In some embodiments of the present application, in the polymerized monomers of the first organic polymer, the mass ratio of the first polymerized monomer, the second polymerized monomer, and the third polymerized monomer is 1:0.05-0.5:0.05-0.5, and can be optionally 1:0.056-0.5:0.056-0.5. Therefore, by controlling the first polymerized monomer, the second polymerized monomer, and the third polymerized monomer in the preparation of the first organic polymer to be within the above-mentioned mixing ratio, the present application can not only improve the adhesion of the polymer, but also adjust the glass transition temperature of the first organic polymer to an appropriate range. At the same time, the carboxyl group contained in the second polymerized monomer can form a binding force with the functional groups on the electrode and the isolation membrane material, thereby improving the bonding effect between the electrode and the isolation membrane.
[0017] In some embodiments of the present application, in the monomers of the second organic polymer, the mass ratio of the first monomer, the third monomer, and the fourth monomer is 1:0.05-0.5:0.05-0.5, and can optionally be 1:0.056-0.5:0.056-0.5. Thus, by controlling the first monomer, the third monomer, and the fourth monomer used to prepare the second organic polymer within the above-mentioned mixing ratio, the present application can not only adjust the glass transition temperature of the second organic polymer, which helps to adjust the glass transition temperature of the second organic polymer to an appropriate range, but also improve the ionic conductivity and adhesion of the second organic polymer.
[0018] In some embodiments of the present application, the first polymerizable monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, or 2-hydroxypropyl methacrylate. Thus, by using the above-mentioned first polymerizable monomer, the glass transition temperature of the polymer can be adjusted and the anti-swelling ability of the polymer can be improved.
[0019] In some embodiments of the present application, the second polymerizable monomer includes at least one of acrylic acid, methacrylic acid, butenoic acid, or heptenoic acid. Thus, the use of the second polymerizable monomer can adjust the adhesive properties of the first polymer, thereby improving the cold-pressed adhesion between the separator and the electrode when the polymer is used in the separator, thereby enhancing the cycling performance of the battery.
[0020] In some embodiments of the present application, the third polymerizable monomer includes at least one of acrylamide, N-methylol acrylamide, or N-butoxymethyl acrylamide. Thus, using the third polymerizable monomer can adjust the molecular weight of the first polymer, thereby improving the cold-pressed adhesion between the separator and the electrode when the polymer is used in the separator, thereby enhancing the battery's cycling performance.
[0021] In some embodiments of the present application, the fourth polymerizable monomer includes at least one of acrylonitrile or methacrylonitrile. Thus, the use of the fourth polymerizable monomer can improve the polymer's adhesion and ionic conductivity. When used in a separator, this polymer can enhance the cold-pressed adhesion between the separator and the electrode, reduce battery resistance, and thus enhance battery cycling performance.
[0022] In some embodiments of the present application, the polymer further includes a dispersant, which includes at least one of sodium polystyrene sulfonate, sodium gluconate, sodium polyacrylate, sodium polymethacrylate, sodium polyphosphate, sodium lignin sulfonate, or sodium polycarboxylate. Thus, when this polymer is used in a separator, it can enhance the cold-press adhesion between the separator and the electrode, improving the battery's cycling performance.
[0023] In some embodiments of the present application, the number average molecular weight of the dispersant is 100-100000, and can be optionally 5000-80000. Therefore, when the polymer is used in the separator, the cold press bonding strength between the separator and the electrode can be improved, thereby improving the cycle performance of the battery.
[0024] In some embodiments of the present application, the mass ratio of the first organic polymer, the second organic polymer, and the dispersant is 1:0.1-10:0.01-2, and optionally 1:0.5-3:0.05-1.5. Thus, when this polymer is used in a separator, it can improve the cold-press adhesion between the separator and the electrode, thereby enhancing the cycle performance of the battery.
[0025] In some embodiments of the present application, the polymer further comprises a butadiene polymer. Thus, when the polymer is used in a separator, the cold press bonding strength between the separator and the electrode can be improved, thereby improving the cycle performance of the battery.
[0026] In some embodiments of the present application, the glass transition temperature of the butadiene polymer is less than or equal to 20° C., and may be less than or equal to 15° C. Therefore, when the polymer is used in a separator, the cold press bonding strength between the separator and the electrode can be improved, thereby improving the cycle performance of the battery.
[0027] In some embodiments of the present application, the volume average particle size Dv50 of the butadiene polymer is 100 nm to 300 nm, optionally 120 nm to 250 nm. Thus, when this polymer is used in a separator, it can improve the cold-pressed adhesion between the separator and the electrode, thereby enhancing the cycle performance of the battery.
[0028] In some embodiments of the present application, the butadiene polymer has a viscosity at 25°C of 10mPa·s to 300mPa·s, optionally 80mPa·s to 200mPa·s. Therefore, when used in a separator, this polymer can enhance the cold-press adhesion between the separator and the electrode, improving the battery's cycling performance.
[0029] In some embodiments of the present application, the butadiene polymer includes at least one of polybutadiene, styrene / butadiene copolymer, or acrylonitrile / butadiene copolymer. Thus, when this polymer is used in a separator, it can improve the cold-pressed adhesion between the separator and the electrode, thereby enhancing the battery's cycling performance.
[0030] In some embodiments of the present application, the mass ratio of the first organic polymer, the second organic polymer, and the butadiene polymer is 1:0.1-10:0.1-10, and optionally 1:0.5-3:0.5-8. Thus, when this polymer is used in a separator, it can improve the cold-press adhesion between the separator and the electrode, thereby enhancing the cycle performance of the battery.
[0031] In some embodiments of the present application, the polymer has a first glass transition temperature and a second glass transition temperature, wherein the first glass transition temperature is less than or equal to 25° C., and the second glass transition temperature is greater than 25° C. Therefore, when the polymer is used in a separator, the cold press bonding strength between the separator and the electrode can be improved, thereby improving the cycle performance of the battery.
[0032] In some embodiments of the present application, the first glass transition temperature is between -80°C and 25°C, and may be between -60°C and 25°C. This facilitates the polymer to exhibit its adhesive properties during the cold pressing process, facilitates the adhesion between the separator and the electrode after cold pressing, and improves the cycle performance of the battery.
[0033] In some embodiments of the present application, the second glass transition temperature is 26° C. to 100° C., and optionally 26° C. to 90° C. Therefore, when the polymer is used on a separator, the winding and unwinding steps of the separator at a certain temperature are facilitated.
[0034] In some embodiments of the present application, the volume average particle size Dv50 of the polymer is 1 μm-15 μm, optionally 5 μm-10 μm. Therefore, when the polymer is used on a separator, it can improve the polymer blocking of the separator's pores and enhance the active ion permeability of the separator.
[0035] In some embodiments of the present application, the polymer has a number particle size distribution Dn10 of 1 μm to 5 μm, optionally 1 μm to 3 μm. Thus, when used on a separator, this polymer can prevent clogging of the separator's pores, improve the separator's active ion permeability, and mitigate the problem of a thick coating formed on the separator, which can affect the energy density of a later-fabricated battery.
[0036] The second aspect of the present application provides a method for preparing the above-mentioned polymer, comprising:
[0037] blending water, an emulsifier, an initiator, a first organic monomer, a second polymerizable monomer, and a third polymerizable monomer to obtain a first polymer emulsion;
[0038] blending water, an emulsifier, an initiator, a first polymerizable monomer, a third polymerizable monomer, and a fourth polymerizable monomer to obtain a second polymer emulsion;
[0039] The first polymer emulsion and the second polymer emulsion are mixed to obtain a polymer.
[0040] Thus, the above-mentioned polymer with excellent cold-pressing adhesion can be prepared by this method. When the polymer is used in a separator, the cold-pressing adhesion between the separator and the electrode can be improved, thereby improving the cycle performance of the battery.
[0041] In some embodiments of the present application, a dispersant and / or a butadiene polymer is added during the mixing of the first and second polymer emulsions. Thus, when this polymer is used in a separator, it can enhance the cold-press adhesion between the separator and the electrode, thereby improving the battery's cycling performance.
[0042] In a third aspect, the present application provides a separator, comprising the aforementioned polymer or a polymer obtained by the aforementioned method, thereby improving the cold-pressing adhesion between the separator and the electrode, thereby improving the cycle performance of the battery.
[0043] In a fourth aspect, the present application provides a pole piece comprising the aforementioned polymer or a polymer obtained by the aforementioned method, thereby improving the cold-pressing adhesion between the pole piece and the separator, thereby enhancing the cycle performance of the battery.
[0044] In a fifth aspect, the present application provides a battery comprising the aforementioned separator and / or the aforementioned electrode, thereby providing the battery with excellent cycle performance.
[0045] In a sixth aspect, the present application provides an electrical device comprising the above-mentioned battery, thereby having excellent cycle performance and safety performance.
[0046] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become obvious from the description below, or will be learned through practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0048] FIG1 is a schematic diagram of a battery according to one embodiment of the present application.
[0049] FIG. 2 is an exploded view of the battery according to one embodiment of the present application shown in FIG. 1 .
[0050] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0051] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.
[0052] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.
[0053] FIG6 is a schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.
[0054] Explanation of reference numerals: 1 battery; 11 housing; 12 electrode assembly; 13 cover plate; 2 battery module; 3 battery pack; 31 upper case; 32 lower case. DETAILED DESCRIPTION
[0055] The following embodiments of the technical solution of the present application are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only used as examples and are not intended to limit the scope of protection of the present application.
[0056] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0057] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0058] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0059] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0060] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0061] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0062] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0063] Currently, market developments indicate that secondary batteries are becoming increasingly widely used. They are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but are also widely used in electric vehicles like electric bicycles, electric motorcycles, and electric vehicles, as well as in military equipment and aerospace. As the application of secondary batteries continues to expand, market demand is also growing.
[0064] The battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator. The battery cell has a certain hardness. That is, because the positive and negative electrode sheets and the separator are bonded together and support each other, a structure with a certain thickness is formed. A structure with a certain thickness has a certain hardness. The negative electrode will expand during the charge and discharge process. If the bonding force is weak, a gap will form between the positive and negative electrode sheets and the separator. The positive and negative electrode sheets and the separator cannot adhere to each other and support each other, causing the battery cell to become loose and the hardness to decrease. At this time, the battery's cycle performance deteriorates, which directly leads to a shortened battery life. Electric vehicles need to frequently replace batteries, and consumers spend more on electric vehicles.
[0065] The isolation membrane and the electrode are tightly fitted, which can improve the discharge capacity of the battery, reduce internal resistance, reduce polarization loss, extend the cycle life of the battery, and improve the utilization rate of the secondary battery. The commonly used binder on the existing isolation membrane is polyvinylidene fluoride, but the price of polyvinylidene fluoride has increased sharply at this stage, and the market supply is tight. At the same time, a hot pressing process is required (heating is performed during the pressing process after the isolation membrane and the electrode are stacked) to make the isolation membrane and the electrode tightly bonded. However, after the hot pressing process, the adhesion between the isolation membrane and the positive and negative electrode sheets is too strong. During the battery cycle, excessive expansion of the negative electrode will cause the positive electrode active material in the positive electrode sheet or the negative electrode active material in the negative electrode sheet to be torn off, that is, the positive and negative electrode sheets are demolded, thereby reducing the cycle performance of the battery.
[0066] The polymer of the present application includes a first organic polymer and a second organic polymer, wherein the polymerization monomers of the first organic polymer include a first polymerization monomer, a second polymerization monomer, and a third polymerization monomer, and the polymerization monomers of the second organic polymer include the first polymerization monomer, the third polymerization monomer, and a fourth polymerization monomer, and the structure of the first polymerization monomer includes: R1 includes a hydrogen atom or an alkyl group of 1 to 18 carbon atoms, R2 includes an alkyl group of 1 to 18 carbon atoms, and the structure of the second polymerizable monomer includes: R3 includes a hydrogen atom, a substituted or unsubstituted alkyl group of 1 to 18 carbon atoms; the structure of the third polymerizable monomer includes: R4 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 includes a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms; the structure of the fourth polymerizable monomer includes: R6 includes a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0067] The first organic polymer prepared using the first, second, and third polymerized monomers has a different glass transition temperature from the second organic polymer prepared using the first, third, and fourth polymerized monomers, and the glass transition temperature of the first organic polymer is lower than that of the second organic polymer. When the polymer is at a temperature between the glass transition temperature of the first organic polymer and the glass transition temperature of the second organic polymer, and no pressure is applied to the polymer, the second organic polymer structure is in a glassy state. It is relatively hard and can serve as the skeleton structure of the polymer powder, making the polymer non-sticky and able to meet the requirements of winding and unwinding the separator. At this temperature, the first organic polymer structure is in a rubbery state and can have a certain degree of "fluidity" after applying a certain pressure. The structure of the polymer, including the first organic polymer, can fully penetrate the pores of the positive and negative electrode sheets and the separator, increasing the mechanical interlocking effect, fully exerting its bonding properties, and thus helping to improve the cycle performance of the battery.
[0068] Therefore, when the polymer of the present application is used in a separator, the polymer has no adhesiveness at a certain temperature, which facilitates the winding and unwinding of the separator. However, after being wound with the positive and negative electrode sheets and then subjected to a cold pressing process (no heating is performed during the pressing process after the separator and the electrode sheets are stacked), the polymer has excellent adhesion, so that the positive and negative electrode sheets and the separator are tightly attached to each other. Therefore, when the polymer of the present application is used in a separator, cold pressing bonding between the separator and the electrode sheet can be achieved, and the adhesion between the electrode sheet and the separator is appropriate, thereby improving the cycle performance of the battery.
[0069] The polymer disclosed in the embodiments of the present application is suitable for batteries, and the batteries disclosed in the embodiments of the present application can be used in electrical devices that use batteries as power sources or various energy storage systems that use batteries as energy storage elements. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0070] In a first aspect, the present application provides a polymer, comprising: a first organic polymer and a second organic polymer, wherein the first organic polymer comprises a first polymerized monomer, a second polymerized monomer, and a third polymerized monomer, and the polymerized monomers of the second organic polymer comprise the first polymerized monomer, the third polymerized monomer, and a fourth polymerized monomer, and the structure of the first polymerized monomer comprises:
[0071] wherein R1 comprises a hydrogen atom or an alkyl group of 1 to 18 carbon atoms, and R2 comprises an alkyl group of 1 to 18 carbon atoms,
[0072] The structure of the second polymerizable monomer comprises:
[0073] wherein R3 comprises a hydrogen atom, a substituted or unsubstituted alkyl group of 1 to 18 carbon atoms;
[0074] The structure of the third polymerizable monomer comprises:
[0075] wherein R4 comprises a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 comprises a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms;
[0076] The structure of the fourth polymerized monomer comprises:
[0077] Wherein, R6 includes a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0078] The polymer of the present application includes a first organic polymer and a second organic polymer, wherein the monomers of the first organic polymer include a first polymerized monomer, a second polymerized monomer, and a third polymerized monomer, wherein the first polymerized monomer includes an unsaturated ester group, the second polymerized monomer includes an unsaturated carboxyl group, and the structure of the third polymerized monomer includes an unsaturated amide group. By polymerizing the first polymerized monomer, the second polymerized monomer, and the third polymerized monomer to prepare the first organic polymer, not only can the adhesion of the polymer be improved, but also the glass transition temperature of the first organic polymer can be adjusted within a suitable range. At the same time, the carboxyl group contained in the second polymerized monomer can form a binding force with the functional groups on the electrode and the isolation membrane material, thereby improving the bonding effect between the electrode and the isolation membrane. The monomers of the second organic polymer include the first polymerized monomer, the third polymerized monomer, and the fourth polymerized monomer, wherein the structure of the fourth polymerized monomer includes an unsaturated cyano group. By polymerizing the first polymerized monomer, the third polymerized monomer, and the fourth polymerized monomer to prepare the second organic polymer, not only can the glass transition temperature of the second organic polymer be adjusted, which helps to adjust the glass transition temperature of the second organic polymer within a suitable range, but also can improve the ionic conductivity and adhesion of the second organic polymer.
[0079] The first organic polymer prepared using the first, second, and third polymerized monomers has a different glass transition temperature than the second organic polymer prepared using the first, third, and fourth polymerized monomers, and the glass transition temperature of the first organic polymer is lower than that of the second organic polymer. When the polymer is at a temperature between the glass transition temperature of the first organic polymer and the glass transition temperature of the second organic polymer, and no pressure is applied to the polymer, the second organic polymer structure is in a glassy state. It is relatively hard and can serve as the skeleton structure of the polymer powder, making the polymer non-sticky and able to meet the requirements of winding and unwinding the separator. At this temperature, the first organic polymer structure is in a rubbery state and can have a certain degree of "fluidity" after applying a certain pressure. The structure of the polymer, including the first organic polymer, can fully penetrate the pores of the positive and negative electrode sheets and the separator, increasing the mechanical interlocking effect and fully utilizing its bonding properties, thereby helping to improve the battery.
[0080] Therefore, when the polymer of the present application is used in a separator, the polymer has no adhesive properties at a certain temperature, which facilitates the winding and unwinding of the separator. However, after being wound with the positive and negative electrode sheets and then subjected to a cold pressing process, the polymer has excellent adhesion, allowing the positive and negative electrode sheets and the separator to adhere tightly to each other. Therefore, when the polymer of the present application is used in a separator, the cold pressing adhesion between the separator and the positive and negative electrode sheets can be improved, and the adhesion between the electrode sheets and the separator can be appropriate, thereby improving the cycle performance of the battery.
[0081] In some embodiments of the present application, the structure of the first polymerizable monomer includes:
[0082] Among them, R1 includes a hydrogen atom or an alkyl group with 1-18 carbon atoms, R2 includes an alkyl group with 1-18 carbon atoms, and the first polymerized monomer includes an unsaturated ester group, which is beneficial to the polymerization of the monomer and can improve the anti-swelling ability of the polymer. It also serves as a flexible monomer segment in the molecular chain segment and can adjust the glass transition temperature of the organic polymer, which helps to adjust the glass transition temperature of the first organic polymer and the second organic polymer within a suitable range.
[0083] As an example, an alkyl group with 1-18 carbon atoms can be understood as an alkyl group with 1-18 carbon atoms, such as methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), tert-butyl (-C(CH3)3), n-pentyl (-CH2CH2CH2CH2CH3), n-hexyl (-CH2CH2CH2CH2CH2CH3), etc.
[0084] In some embodiments of the present application, the first polymerizable monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, or 2-hydroxypropyl methacrylate. Thus, by using the first polymerizable monomer described above, the glass transition temperature of the first organic polymer and the second organic polymer can be adjusted, thereby improving the anti-swelling ability of the polymers.
[0085] In some embodiments of the present application, the structure of the second polymerizable monomer includes:
[0086] Wherein, R3 comprises a hydrogen atom, or a substituted or unsubstituted alkyl group of 1 to 18 carbon atoms. Thus, the inclusion of an unsaturated carboxyl group in the second polymerizable monomer facilitates polymerization of the monomer. Using the second polymerizable monomer containing a carboxyl group during the preparation of the first organic polymer allows the carboxyl group to form a bond with the functional groups on the electrode and the separator during the cold pressing process, thereby improving the bonding effect.
[0087] It should be noted that the substituted alkyl group of 1-18 carbon atoms can be understood as a group in which at least one hydrogen atom on an alkyl group with 1-18 carbon atoms is replaced by other groups, such as -CH2OH, -CH2CH2OH, -CH2CH2CH2OH, -CH(CH2OH)2, -CH2CH2CH2CH2OH, -C(CH2OH)3, -CH2CH2CH2CH2CH2OH, etc.
[0088] In some embodiments of the present application, the second polymerizable monomer includes at least one of acrylic acid, methacrylic acid, crotonic acid, or heptenoic acid. Thus, the adhesive properties of the first organic polymer can be adjusted by using the second polymerizable monomer described above.
[0089] In some embodiments of the present application, the structure of the third polymerized monomer includes:
[0090] R4 comprises a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 comprises a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms. Thus, the structure of the third polymerizable monomer includes an unsaturated amide group, which facilitates polymerization of the monomers. Furthermore, this type of monomer can adjust the molecular weight of the first organic polymer, thereby improving the polymer's adhesive properties.
[0091] It should be noted that the alkyl group of 1-6 carbon atoms substituted by hydroxyl groups can be understood as a group in which at least one hydrogen atom on an alkyl group with 1-6 carbon atoms is replaced by a hydroxyl group, for example -CH2OH, -CH2CH2OH, -CH2CH2CH2OH, -CH(CH2OH)2, -CH2CH2CH2CH2OH, -C(CH2OH)3, -CH2CH2CH2CH2CH2OH, etc. At the same time, the alkoxy group of 1-6 carbon atoms substituted by hydroxyl groups can be understood as a group in which at least one hydrogen atom on an alkoxy group with 1-6 carbon atoms is replaced by a hydroxyl group, for example, methoxy (HOCH2O-), ethoxy (OHCH2CH2O-), propoxy (OHCH2CH2CH2O-), etc.
[0092] In some embodiments of the present application, the third polymerizable monomer includes at least one of acrylamide, N-methylol acrylamide, or N-butoxymethyl acrylamide. Thus, the use of the third polymerizable monomer can adjust the molecular weight of the polymer, thereby improving the adhesion of the polymer.
[0093] In some embodiments of the present application, the structure of the fourth polymerized monomer includes:
[0094] Wherein, R6 includes a hydrogen atom or an alkyl group with 1 to 6 carbon atoms. Thus, the structure of the fourth polymerizable monomer includes an unsaturated cyano group, which is beneficial to the polymerization of the monomer and improves the ionic conductivity and adhesion of the second organic polymer.
[0095] In some embodiments of the present application, the fourth polymerizable monomer includes at least one of acrylonitrile or methacrylonitrile. Thus, the use of the fourth polymerizable monomer can improve the ionic conductivity and annual adhesion of the polymer.
[0096] In some embodiments of the present application, the mass ratio of the first organic polymer to the second organic polymer is 1:(0.1-10), for example, 1:(0.5-9.5), 1:(1-9), 1:(1.5-8.5), 1:(2-8), 1:(2.5-7.5), 1:(3-7), 1:(3.5-6.5), 1:(4-6), 1:(4.5-5.5), 1:(5-5.5), etc.
[0097] The polymer of the present application is a secondary particle formed by the aggregation of primary particles of a first organic polymer and primary particles of a second organic polymer. Both the primary particles of the first organic polymer and the primary particles of the second organic polymer have the opportunity to be exposed on the surface of the secondary particles. By regulating the mass ratio of the first organic polymer and the second organic polymer, the opportunity of the first organic polymer to be exposed on the surface of the secondary particles is regulated to adjust the cohesiveness of the polymer. Thus, by setting the mass ratio of the first organic polymer to the second organic polymer in the above range, at a certain temperature, the polymer can be made to have both a rubbery state and a glassy state, wherein the glassy structure is relatively hard. When no pressure is applied to the polymer, the glassy structure can serve as the skeleton structure of the polymer powder, making the polymer non-sticky and able to meet the requirements of winding and unwinding the isolation membrane. The structure of the polymer structure in the rubbery state can have a certain "fluidity" after applying a certain pressure. The structure in the rubbery state in the polymer can fully penetrate into the pores of the positive and negative pole pieces and the isolation membrane, increasing the mechanical interlocking effect, which can give full play to its bonding performance, thereby helping to improve the cycle performance of the battery. At the same time, the above composition is not too hard to affect the bonding effect between the isolation membrane and the pole piece. In other embodiments of the present application, the mass ratio of the first organic polymer to the second organic polymer is 1:(0.5-3).
[0098] In some embodiments of the present application, in the polymerization monomer of the first organic polymer, the mass ratio of the first polymerization monomer, the second polymerization monomer and the third polymerization monomer is 1:0.05-0.5:0.05-0.5, for example, 1:0.1-0.5:0.05-0.5, 1:0.15-0.45:0.05-0.5, 1:0.2-0.4:0.05-0.5, 1:0.15-0.45:0.05-0.5 :0.25-0.35:0.05-0.5, 1:0.3-0.35:0.05-0.5, 1:0.05-0.5:0.1-0.5, 1:0.05-0.5:0.15-0.45, 1:0.05-0.5:0.2-0.4, 1:0.05-0.5:0.25-0.35, 1:0.05-0.5:0.3-0.35, etc. Thus, the present application controls the first polymerized monomer, the second polymerized monomer and the third polymerized monomer for preparing the first organic polymer to be within the above-mentioned mixing ratio, which not only improves the adhesion of the polymer, but also adjusts the glass transition temperature of the first organic polymer to be within a suitable range. At the same time, the carboxyl group contained in the second polymerized monomer can form a binding force with the functional groups on the electrode and the isolation membrane material, thereby improving the bonding effect between the electrode and the isolation membrane. In some other embodiments of the present application, in the polymerization monomers of the first organic polymer, the mass ratio of the first polymerization monomer, the second polymerization monomer and the third polymerization monomer is 1:0.056-0.5:0.056-0.5.
[0099] In some embodiments of the present application, in the polymerization monomers of the second organic polymer, the mass ratio of the first polymerization monomer, the third polymerization monomer and the fourth polymerization monomer is 1:0.05-0.5:0.05-0.5, for example, 1:0.1-0.5:0.05-0.5, 1:0.15-0.45:0.05-0.5, 1:0.2-0.4:0.05-0.5, 1:0.15-0.45:0.05-0.5 :0.25-0.35:0.05-0.5, 1:0.3-0.35:0.05-0.5, 1:0.05-0.5:0.1-0.5, 1:0.05-0.5:0.15-0.45, 1:0.05-0.5:0.2-0.4, 1:0.05-0.5:0.25-0.35, 1:0.05-0.5:0.3-0.35, etc. Thus, the present application controls the first polymerized monomer, the third polymerized monomer, and the fourth polymerized monomer for preparing the second organic polymer to be within the above-mentioned mixing ratio, which not only can adjust the glass transition temperature of the second organic polymer, but also helps to adjust the glass transition temperature of the second organic polymer to an appropriate range, and can also improve the ionic conductivity and adhesion of the second organic polymer. In some other embodiments of the present application, in the polymerized monomers of the second organic polymer, the mass ratio of the first polymerized monomer, the third polymerized monomer, and the fourth polymerized monomer is 1:0.056-0.5:0.056-0.5.
[0100] It should be noted that the first polymerized monomer used in the preparation of the first organic polymer in this application may be the same as or different from the first polymerized monomer used in the preparation of the second organic polymer. Similarly, the third polymerized monomer used in the preparation of the first organic polymer may be the same as or different from the third polymerized monomer used in the preparation of the second organic polymer. Those skilled in the art can make a selection based on actual needs.
[0101] In some embodiments of the present application, the polymer further includes a dispersant, and the dispersant includes at least one of sodium polystyrene sulfonate, sodium gluconate, sodium polyacrylate, sodium polymethacrylate, sodium polyphosphate, sodium lignin sulfonate or sodium polycarboxylate.
[0102] The dispersant of the above composition is added to the polymer of the present application, which has good dispersing properties for the suspension system and reduces the irregular coagulation of the emulsion system. When the polymer is used for the isolation membrane, the cold pressing bonding strength between the isolation membrane and the electrode can be improved, thereby improving the cycle performance of the battery.
[0103] In some embodiments of the present application, the number average molecular weight of the dispersant is 100-100,000, for example, 500-100,000, 3,000-100,000, 5,000-100,000, 8,000-100,000, 10,000-100,000, 30,000-90,000, 50,000-70,000, 50,000-60,000, 55,000-60,000, etc. Thus, the present application adds a dispersant of the above molecular weight to the polymer to reduce the irregular coagulation of the emulsion system. When the polymer is used for the isolation membrane, the cold pressing adhesion between the isolation membrane and the pole piece can be improved, thereby improving the hardness of the battery cell and the cycle performance of the battery. In some embodiments of the present application, the number average molecular weight of the dispersant is 5,000-80,000.
[0104] In this application, the number average molecular weight of a polymer can be determined by gel permeation chromatography (GPC) according to standard GB / T 21863-2008. Specifically, this method can be performed using an ACQUITY APC ultra-high performance polymer chromatograph and an ACQUITY differential refractive index (RI) detector. Standards: polystyrene sleeves; run time: 30 minutes; detector: ACQUITY differential refractive index (RI) detector; column oven temperature: 90°C; detector temperature: 55°C. Sample testing: a. Standard sample and test sample preparation: Weigh 0.002g to 0.004g of standard sample / test sample respectively and add 2mL of mobile phase liquid to prepare a 0.1% to 0.5% mixed standard, and place in the refrigerator for >8h; b. Standard solution / sample testing: Edit the sample group to be tested, select the established sample group method, wait for the baseline to stabilize, click the run queue, and start testing the sample; (4) Data processing: Based on the relationship between retention time and molecular weight, use the chemical workstation to establish a calibration curve, integrate and quantify the sample spectrum, and the chemical workstation automatically generates the number average molecular weight result.
[0105] In some embodiments of the present application, the mass ratio of the first organic polymer, the second organic polymer and the dispersant is 1:0.1-10:0.01-2, for example, 1:0.5-10:0.01-2, 1:1-10:0.01-2, 1:2-9:0.01-2, 1:3-8:0.01-2, 1:4-7:0.01-2, 1:5-6:0.01-2, 1:0.1-10:0.05-2, 1:0.1-10:0.08-2, 1:0.1-10:0.1-2, 1:0.1-10:0.3-1.8, 1:0.1-10:0.5-1.5, 1:0.1-10:0.7-1.2, 1:0.1-10:1-1.2, etc. Therefore, the polymer of the present application, comprising the first organic polymer, the second organic polymer, and the dispersant in the aforementioned mixing ratio, can significantly reduce irregular aggregation of the emulsion system. When used in a separator, this polymer can improve the cold-pressed adhesion between the separator and the electrode, thereby improving the hardness of the battery cell and the cycle performance of the battery. In other embodiments of the present application, the mass ratio of the first organic polymer, the second organic polymer, and the dispersant is 1:0.5-3:0.05-1.5.
[0106] In some embodiments of the present application, the polymer also includes a butadiene polymer. Specifically, the weak point of the bonding between the separator and the pole piece lies in the bonding force between the separator and the cathode pole piece, and the commonly used binder in the cathode pole piece is styrene-butadiene rubber (SBR). SBR has the characteristics of super strong alkali resistance, soft film formation and good air permeability, strong bonding force, etc. In addition, the cathode pole piece generally has the phenomenon of binder floating up, that is, a part of SBR will be enriched on the surface of the cathode pole piece. The present application adds a butadiene polymer to the polymer. The polymer contains a butadiene polymer and the SBR binder enriched on the surface of the cathode pole piece belongs to the same substance, which can improve the bonding strength between the two phases. Therefore, by adding a butadiene copolymer to the polymer and using the polymer for the separator, the cold pressing bonding force between the separator and the cathode pole piece can be improved, thereby improving the cycle performance of the battery.
[0107] In some embodiments of the present application, the glass transition temperature of the butadiene polymer is less than or equal to 20°C, for example, 5°C-20°C, 7°C-17°C, 10°C-15°C, etc. Therefore, a butadiene polymer with a glass transition temperature less than or equal to 20°C is used, and its glass transition temperature is lower than room temperature and is in a rubbery state at room temperature, making the polymer more "fluid" when cold-pressed at room temperature, and able to better penetrate into the gaps on the surface of the electrode, increasing the mechanical interlocking effect, while being able to fully contact with the SBR on the surface of the cathode electrode, improving adhesion. In other embodiments of the present application, the glass transition temperature of the butadiene polymer is less than or equal to 15°C.
[0108] In some embodiments of the present application, the butadiene polymer has a volume average particle size (Dv50) of 100 nm to 300 nm, for example, 150 nm to 250 nm, 150 nm to 200 nm, etc. Consequently, when used in a separator, this polymer can improve the cold-press adhesion between the separator and the electrode, while also providing adequate adhesion between the separator and the electrode, thereby enhancing the battery's cycling performance. In some embodiments of the present application, the butadiene polymer has a Dv50 of 120 nm to 250 nm.
[0109] It should be noted that, in the examples of the present application, the volume average particle size Dv50 of the butadiene polymer is the particle size corresponding to when the cumulative particle size volume distribution percentage reaches 50%, and the test method is:
[0110] Reference standard GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method. Use a laser particle size analyzer (Malvern 3000, MasterSizer 3000) for testing, and use a helium-neon red light source as the main light source. Take a clean small beaker and add 1g of the sample to be tested, add a drop of surfactant, add 20ml of deionized water (the sample concentration ensures that the shading degree is 8-12%), and ultrasonicate at 53KHz / 120W for 5 minutes to ensure that the sample is completely dispersed. Turn on the laser particle size analyzer, clean the optical path system, and automatically test the background. Stir the ultrasonicated test solution to make it evenly dispersed, put it into the sample cell as required, start measuring the particle size, and read the measurement results from the instrument.
[0111] In some embodiments of the present application, the viscosity of the butadiene polymer at 25°C is 10mPa·s-300mPa·s, for example, 50mPa·s-250mPa·s, 100mPa·s-200mPa·s, 150mPa·s-220mPa·s, etc. Thus, by using a butadiene polymer with this viscosity, the compatibility of the butadiene polymer with the first organic polymer and the second organic polymer can be improved. When the polymer is used in a separator, the cold press bonding strength between the separator and the pole piece can be improved, and the bonding strength between the separator and the pole piece is suitable, thereby improving the cycle performance of the battery. In other embodiments of the present application, the viscosity of the butadiene polymer at 25°C is 80mPa·s-200mPa·s.
[0112] It should be noted that in the examples of this application, the viscosity of butadiene polymers at 25°C is measured in accordance with the national standard GB / T10247-2008, "Methods for Measuring Viscosity." Specifically, at 25°C, a Brookfield viscometer is used. The shear force exerted on a 62# rotor as it rotates continuously at a constant speed within the sample causes the spring to generate torque, which is proportional to the viscosity, to obtain the viscosity value.
[0113] In some embodiments of the present application, the butadiene polymer includes at least one of polybutadiene, styrene / butadiene copolymer, or acrylonitrile / butadiene copolymer. Therefore, when the butadiene polymer of the above composition is used in the polymer, the cold press bonding strength between the separator and the electrode can be improved, and the bonding strength between the separator and the electrode can be suitable, thereby improving the cycling performance of the battery.
[0114] In some embodiments of the present application, the mass ratio of the first organic polymer, the second organic polymer and the butadiene polymer is 1:0.1-10:0.1-10, for example, 1:0.5-10:0.1-10, 1:1-10:0.1-10, 1:2-9:0.1-10, 1:3-8:0.1-10, 1:4-7:0.1-10, 1:5-6:0.1-10, 1:0.1-10:0.5-10, 1:0.1-10:1-10, 1:0.1-10:2-9, 1:0.1-10:3-8, 1:0.1-10:4-7, 1:0.1-10:5-6, etc. Thus, the polymer of the present application includes the first organic polymer, the second organic polymer, and the butadiene polymer in the aforementioned mixing ratio. When used in a separator, this polymer can improve the cold-pressed adhesion between the separator and the electrode, thereby improving the hardness of the battery cell and the cycle performance of the battery. In other embodiments of the present application, the mass ratio of the first organic polymer, the second organic polymer, and the butadiene polymer is 1:0.5-3:0.5-8.
[0115] It should be noted that the polymer of the present application may include the first organic polymer, the second organic polymer and the dispersant at the same time, or include the first organic polymer, the second organic polymer and the butadiene polymer at the same time, or include the first organic polymer, the second organic polymer, the dispersant and the butadiene polymer at the same time.
[0116] In some embodiments of the present application, the polymer has a first glass transition temperature and a second glass transition temperature, wherein the first glass transition temperature is less than or equal to 25° C., and the second glass transition temperature is greater than 25° C. Specifically, the first organic polymer of the present application corresponds to the first glass transition temperature, and the second organic polymer corresponds to the second glass transition temperature.
[0117] The glass transition temperature (Tg) is the temperature at which a polymer changes from an elastic state to a glassy state. It refers to the transition temperature of an amorphous polymer (including the non-crystalline portion of a crystalline polymer) from the glassy state to the elastic state, or vice versa. It is the lowest temperature at which the macromolecular segments of an amorphous polymer can move freely, and is usually denoted by Tg. Above the Tg, a polymer exhibits elasticity; below the Tg, it exhibits brittleness. The Tg can be measured using methods commonly used in the art, such as differential scanning calorimetry (DSC) as described in GB / T 19466.2.
[0118] It can be understood that the first glass transition temperature is less than or equal to 25°C, above which the structure of the polymer including the first organic polymer is in a rubbery state, and the second glass transition temperature is greater than 25°C, below which the structure of the second organic polymer in the polymer is in a glassy state.
[0119] For example, the first glass transition temperature is lower than room temperature, and the second glass transition temperature is higher than room temperature. At room temperature, when no pressure is applied to the polymer, the second glass transition temperature is higher than room temperature, and the structure of the polymer including the second organic polymer is in a glassy state, which is relatively hard and can serve as the skeleton structure of the polymer powder, making the polymer non-sticky; at room temperature, the first glass transition temperature is lower than room temperature, and the structure of the polymer including the first organic polymer is in a rubbery state, and can have a certain "fluidity" after applying a certain pressure. The structure of the first organic polymer in the polymer can fully penetrate into the pores of the positive and negative pole pieces and the isolation membrane, increasing the mechanical interlocking effect, and can give full play to its bonding performance, thereby helping to improve the cycle performance of the battery.
[0120] It can be understood that when the temperature is above the first glass transition temperature, the structure of the polymer including the first organic polymer is in a soft state and can be deformed with the extrusion force, while the structure of the isolation membrane and the electrode has pores. As the extrusion force acts on the polymer, part of the structure of the first organic polymer can penetrate into the pores of the isolation membrane and the electrode, bonding the isolation membrane and the polymer together, achieving a mechanical interlocking effect and realizing the bonding function.
[0121] Due to the significant difference in glass transition temperatures between the first and second organic polymers in the polymer, when cold-pressed at a temperature between the first and second glass transition temperatures, the structure of the first organic polymer in the polymer is in a rubbery state, while the structure of the second organic polymer in the polymer is in a glassy state, giving the polymer both soft and hard properties. When coated on a separator, at a temperature between the first and second glass transition temperatures and without applied pressure, the polymer is non-sticky, enabling the separator to be wound and unwound. When a certain pressure is applied, the polymer exhibits pressure sensitivity and exhibits excellent adhesion, meeting the bonding requirements between the separator and the positive and negative electrodes.
[0122] Therefore, when the polymer of the present application is applied to the separator, the polymer becomes non-sticky at temperatures between the first and second glass transition temperatures, facilitating winding and unwinding of the separator. However, after being wound with the positive and negative electrode sheets and subjected to a cold pressing process, the polymer exhibits excellent adhesion, allowing the positive and negative electrode sheets to adhere tightly to each other with the separator. Therefore, when the polymer of the present application is used in the separator, the cold pressing adhesion between the separator and the positive and negative electrode sheets can be improved, thereby improving the hardness of the battery cell and the battery cycle performance.
[0123] In some embodiments of the present application, the first glass transition temperature can be any value such as -100°C, -90°C, -80°C, -70°C, -50°C, -30°C, -10°C, 10°C, 20°C, 24°C, 25°C, and the range value between any two of the above point values, without specific limitation.
[0124] In some embodiments of the present application, the second glass transition temperature can be any value such as 26°C, 30°C, 50°C, 80°C, 100°C, 200°C, and a range value between any two of the above point values, without specific limitation.
[0125] In some embodiments of the present application, the first glass transition temperature range is -80°C to 25°C, preferably -60°C to 25°C.
[0126] Within the above range, the polymer includes a structure with a first glass transition temperature and is in a rubbery state above the first glass transition temperature, which is conducive to exerting its adhesion during the cold pressing process, and is conducive to the adhesion between the isolation membrane and the electrode after cold pressing, thereby improving the performance of the battery.
[0127] In the above-mentioned range of -80℃ to 25℃, the values include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and -80℃, -70℃, -60℃, -50℃, -40℃, -30℃, -20℃, -10℃, 0℃, 10℃, 20℃, 25℃, etc., as well as the range values between any two of the above-mentioned point values.
[0128] In the above-mentioned range of -60℃ to 25℃, the values include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and -60℃, -50℃, -40℃, -30℃, -20℃, -10℃, 0℃, 10℃, 20℃, 25℃, etc., as well as the range values between any two of the above-mentioned point values.
[0129] In some embodiments of the present application, the second glass transition temperature range is 26°C to 100°C, preferably 26°C to 90°C.
[0130] Within the above range, the structure including the second glass transition temperature in the polymer is in a glassy state below the second glass transition temperature, which is beneficial as the skeleton structure of the polymer at a temperature between the first glass transition temperature and the second glass transition temperature, making the polymer non-sticky and facilitating the operation of the winding and unwinding steps of the isolation film at a certain temperature.
[0131] In the above-mentioned 26°C to 100°C, the values include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 26°C, 28°C, 30°C, 50°C, 80°C, 90°C, 100°C, etc., as well as the range values between any two of the above-mentioned point values.
[0132] In the above-mentioned 26°C to 90°C, the values include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 26°C, 28°C, 30°C, 50°C, 80°C, 90°C, etc., as well as the range values between any two of the above-mentioned point values.
[0133] In some embodiments of the present application, the volume particle size distribution Dv50 of the polymer is 1 μm-15 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc. In the present application, when a polymer meeting the above volume average particle size Dv50 is used in an isolation membrane, it can not only reduce the risk of the polymer clogging the isolation membrane pores, but also reduce the problem of the polymer coating on the isolation membrane forming a thicker coating and affecting the energy density of the battery prepared later. In other embodiments of the present application, the volume particle size distribution Dv50 of the polymer is 5 μm-10 μm.
[0134] It should be noted that, in the examples of the present application, the volume average particle size Dv50 of the polymer is the particle size corresponding to when the cumulative particle size volume distribution percentage reaches 50%, and the test method is:
[0135] Reference standard GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method. Use a laser particle size analyzer (Malvern 3000, MasterSizer 3000) for testing, and use a helium-neon red light source as the main light source. Take a clean small beaker and add 1g of the sample to be tested, add a drop of surfactant, add 20ml of deionized water (the sample concentration ensures that the light shielding is 8-12%), and ultrasonicate at 53KHz / 120W for 5 minutes to ensure that the sample is completely dispersed. Turn on the laser particle size analyzer, clean the optical path system, and automatically test the background. Stir the ultrasonicated test solution to make it evenly dispersed, place it in the sample cell as required, and start measuring the particle size. The measurement results can be read from the instrument.
[0136] In some embodiments of the present application, the number particle size distribution Dn10 of the polymer is 1μm-5μm, for example, 1μm, 2μm, 3μm, 4μm, 5μm, etc. In the present application, when a polymer that satisfies the above number particle size distribution Dn10 is used for an isolation membrane, it can not only improve the risk of the polymer clogging the pores of the isolation membrane, but also improve the problem of the polymer being coated on the isolation membrane to form a thicker coating, which affects the energy density of the battery prepared later. Therefore, when the polymer is used on the isolation membrane, it can improve the polymer clogging the pores of the isolation membrane, improve the active ion permeability of the isolation membrane, and improve the problem of the polymer being coated on the isolation membrane to form a thicker coating, which affects the low energy density of the battery prepared later. In other embodiments of the present application, the number particle size distribution Dn10 of the polymer is 1μm-3μm.
[0137] It should be noted that in the examples of the present application, the number particle size distribution Dn10 of the polymer is the particle size corresponding to when the cumulative number distribution percentage of the particles reaches 10%. The test method can refer to GB / T 19077-2016 and use a Malvern laser particle size analyzer for characterization testing, such as the Malvern Mastersizer-3000.
[0138] The second aspect of the present application provides a method for preparing the above-mentioned polymer, comprising:
[0139] blending water, an emulsifier, an initiator, a first organic monomer, a second polymerizable monomer, and a third polymerizable monomer to obtain a first polymer emulsion;
[0140] blending water, an emulsifier, an initiator, a first polymerizable monomer, a third polymerizable monomer, and a fourth polymerizable monomer to obtain a second polymer emulsion;
[0141] The first polymer emulsion and the second polymer emulsion are mixed to obtain a polymer.
[0142] The first organic polymer is produced by emulsion polymerization of a first polymerizable monomer, a second polymerizable monomer, and a third polymerizable monomer. The second organic polymer is produced by emulsion polymerization of the first polymerizable monomer, a third polymerizable monomer, and a fourth polymerizable monomer. The first and second organic polymers produced using the above monomers have suitable first and second glass transition temperatures. Coating the polymers on the separator ensures both room temperature non-adhesiveness and cold-pressed adhesion between the separator and the positive and negative electrodes during the cold-pressing process. This improves the hardness of the battery cell and addresses issues such as cell opening and soft cells. Furthermore, when the polymers are coated on the separator and applied to the battery, the adhesion between the separator and the positive and negative electrodes is suitable, thereby improving the battery's cycle performance.
[0143] The present invention obtains a first polymer emulsion and a second polymer emulsion by emulsion polymerization, and obtains a polymer by spray drying, that is, the polymer includes a first organic polymer and a second organic polymer.
[0144] Emulsion polymerization is a process in which monomers are dispersed in water with the help of emulsifiers and mechanical stirring to form an emulsion, and then an initiator is added to initiate monomer polymerization.
[0145] Emulsifiers are substances that can transform mutually incompatible oils and water into an emulsion that is difficult to separate. Emulsifiers are typically surfactants that have both hydrophilic polar groups and hydrophobic (lipophilic) non-polar groups. For example, the emulsifier can be at least one of sodium dodecylsulfonate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium laurate, sodium stearate, or sodium palmitoleate.
[0146] An initiator is a substance that can initiate polymerization of monomers. For example, a free radical initiator refers to a class of compounds that readily decompose into free radicals (i.e., primary free radicals) upon heating and can be used to initiate free radical polymerization and copolymerization of olefinic and diene monomers. For example, the initiator can be at least one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, dimethyl azobisisobutyrate, benzoyl peroxide, or dioctanoyl peroxide.
[0147] Water, emulsifier, initiator, and monomers constituting the polymer are blended and stirred. The water and emulsifier are stirred and dispersed to form an emulsion, that is, the emulsifier forms micelles in the aqueous phase, and most of the micelles are solubilized with monomers. Under heating conditions, the initiator initiates polymerization of the monomers inside the micelles to obtain an emulsion.
[0148] Spray drying, through mechanical action, disperses the material to be dried (a mixture of the first polymer emulsion and the second polymer emulsion) into very fine mist-like particles (increasing the water evaporation area and accelerating the drying process), which come into contact with hot air, instantly removing most of the water and drying the solid matter in the material into powder.
[0149] A polymer consisting of the first organic polymer and the second organic polymer is obtained through a spray drying process.
[0150] In some embodiments of the present application, the step of mixing and stirring the first polymer emulsion and the second polymer emulsion and obtaining a polymer by spray drying includes: mixing and stirring the first polymer emulsion and the second polymer emulsion to obtain a mixed emulsion, and the mass ratio of the first organic polymer to the second organic polymer in the mixed emulsion is in the range of 1:(0.1-10), preferably 1:(0.5-3).
[0151] In some embodiments of the present application, the above method further includes: adding a dispersant and / or a butadiene polymer during the mixing process of the first polymer emulsion and the second polymer emulsion. Specifically, the dispersant is added during the mixing process of the first polymer emulsion and the second polymer emulsion of the present application. The dispersant has good dispersing properties for the suspension system and reduces the irregular coagulation of the emulsion system. When the polymer is used for the isolation membrane, the cold pressing adhesion between the isolation membrane and the pole piece can be improved, and the hardness of the battery cell and the cycle performance of the battery can be improved. And when a butadiene copolymer is added during the mixing process of the first polymer emulsion and the second polymer emulsion, when the polymer is used for the isolation membrane, the cold pressing adhesion between the isolation membrane and the pole piece can be improved, and the hardness of the battery cell and the cycle performance of the battery can be improved.
[0152] It should be noted that, in the present application, during the mixing process of the first polymer emulsion and the second polymer emulsion, a dispersant or a butadiene polymer may be added separately, or a dispersant and a butadiene polymer may be added simultaneously.
[0153] Therefore, when the polymer is used for the separator, the cold pressing bonding strength between the separator and the pole piece can be improved, and the bonding strength between the separator and the pole piece is appropriate, thereby improving the cycle performance of the battery.
[0154] In a third aspect, the present application provides a separator comprising the polymer of the first aspect or a polymer obtained using the method of the second aspect. Thus, when the aforementioned polymer is applied to the separator, the cold-pressed adhesion between the separator and the electrode is enhanced, and the adhesion between the separator and the electrode is adequate, thereby improving the cycling performance of the battery.
[0155] In some embodiments of the present application, the isolation film of the present application includes a base film and an adhesive layer, wherein the adhesive layer is formed on at least one side of the base film, and the adhesive layer includes the polymer of the first aspect of the present application or the polymer obtained by the method of the second aspect of the present application. For example, the adhesive layer is formed on opposite sides of the base film.
[0156] In the present application, there is no particular limitation on the type of base membrane, and any known base membrane with a porous structure having good chemical stability and mechanical stability can be selected.
[0157] In some embodiments of the present application, the base film may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The base film may be a single-layer film or a multi-layer composite film, without particular limitation. When the base film is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0158] The isolation membrane described herein can be prepared using conventional methods in the art. For example, the polymer described in the first aspect of the present invention can be dissolved in an organic solvent to obtain a slurry, which can then be coated on a base film and then dried to remove the organic solvent, thereby obtaining the isolation membrane described herein.
[0159] In some embodiments of the present application, the coating density of the polymer on one side of the base film is 0.3 g / m 2 -1.0g / m 2 , for example 0.4g / m 2 -0.9g / m 2 , 0.5g / m 2 -0.8g / m 2 , 0.6g / m 2 -0.7g / m 2 In this way, the bonding strength between the separator and the electrode can be improved, and the safety performance of the battery can be improved. In other embodiments of the present application, the coating density of the polymer on one side of the base film can be 0.3g / m 2 -0.8g / m 2 .
[0160] It should be noted that the test method for the coating density of the polymer on one side of the base film is as follows: the isolation film sprayed with adhesive is cut according to the cutting plate, the length and width of the cut sample are measured to obtain the area S of the sample, and the weight of the isolation film sample sprayed with adhesive is weighed as M1; according to the same method, the isolation film sample of the same area without adhesive coating is cut, the weighed mass is M2, and the isolation film coating density is (M1-M2) / S.
[0161] In a fourth aspect, the present application provides a pole piece, comprising the polymer of the first aspect or a polymer obtained by the method of the second aspect, thereby improving the stability of the pole piece and the cycle performance and safety performance of the battery.
[0162] It should be noted that the electrode described in this application can be a positive electrode or a negative electrode.
[0163] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes the polymer of the first aspect of the present application.
[0164] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.
[0165] In some embodiments of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0166] In some embodiments of the present application, the positive electrode active material may be a positive electrode active material for batteries known in the art.
[0167] As an example, when the positive electrode plate is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05O2) or at least one of its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, or a composite material of lithium iron manganese phosphate and carbon.
[0168] For example, when the positive electrode plate is used in a sodium ion battery, the positive electrode active material may be a positive electrode active material known in the art for use in sodium ion batteries. For example, the positive electrode active material may include, but is not limited to, at least one of a layered transition metal oxide, a polyanion compound, and a Prussian blue analog.
[0169] Examples of the layered transition metal oxides include:
[0170] Na 1-x Cu h Fe k Mn l M 1 m O 2-y , where M 1 Including at least one of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn or Ba, 0 <x≤0.33,0<h≤0.24,0≤k≤0.32,0<l≤0.68,0≤m<0.1,h+k+l+m=1,0≤y<0.2;
[0171] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2 including at least one of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn or Ba, 0 <z≤0.1;
[0172] Na a Li b Ni c Mn d Fe e O2, of which 0.67 <a≤1,0<b<0.2,0<c<0.3,0.67<d+e<0.8,b+c+d+e=1。
[0173] Examples of the polyanionic compound include:
[0174] A 1 f M3 g (PO4) i O j X 1 3-j , wherein A 1 includes at least one of H, Li, Na, K or NH4, M 3 includes at least one of Ti, Cr, Mn, Fe, Co, Ni, V, Cu or Zn, X 1 is at least one of F, Cl or Br, 0 < f ≤ 4, 0 < g ≤ 2, 1 ≤ i ≤ 3, 0 ≤ j ≤ 2;
[0175] Na n M 4 PO4X<00,00066>, wherein M 4 includes at least one of Mn, Fe, Co, Ni, Cu or Zn, X 2 is at least one of F, Cl or Br, 0 < n ≤ 2;
[0176] Na p M 5 q (SO4)3, wherein M 5 includes at least one of Mn, Fe, Co, Ni, Cu or Zn, 0 < p ≤ 2, 0 < q ≤ 2;
[0177] Na s Mn t Fe 3-t (PO4)2(P2O7), wherein 0 < s ≤ 4, 0 ≤ t ≤ 3, for example t is 0, 1, 1.5, 2 or 3.
[0178] As an example of the above Prussian blue analogs, for example, the following can be listed:
[0179] A u M 6 v [M 7 (CN)6] w ·xH2O, wherein A includes H + , NH4 + , at least one of alkali metal cations or alkaline earth metal cations, M 6 and M 7 each independently includes at least one of transition metal cations, 0 < u ≤ 2, 0 < v ≤ 1, 0 < w ≤ 1, 0 < x < 6. For example, A includes H + , Li + , Na + , K + , NH4 + , Rb +、Cs + 、Fr + 、Be 2+ Mg 2+ , Ca 2+ 、Sr 2+ 、Ba 2+ or Ra 2+ At least one of M 6 and M 7 Each independently includes at least a cation of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, or W.
[0180] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0181] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the polymer and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0182] In some embodiments of the present application, based on the total mass of the positive electrode active material layer, the mass proportion of the polymer in the positive electrode sheet is 1%-3%, for example, 1.2%-2.8%, 1.5%-2.5%, 1.8%-2.2%, 2%-2.2%, etc. This can reduce the shedding of the positive electrode sheet, thereby improving the cycle performance of the battery containing the polymer.
[0183] Similarly, the electrode sheet described in the present application may also be a negative electrode sheet. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes the polymer described in the first aspect of the present application or a polymer obtained using the method of the second aspect of the present application.
[0184] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is provided on either or both of the two facing surfaces of the negative electrode current collector.
[0185] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0186] In some embodiments of the present application, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, or silicon alloys. The tin-based material may include at least one of elemental tin, tin oxides, or tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0187] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0188] In some embodiments of the present application, the negative electrode active material layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0189] In some embodiments of the present application, the negative electrode sheet can be prepared by the following method: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the polymer described in the first aspect of the present application are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0190] In some embodiments of the present application, based on the total mass of the negative electrode active material layer, the mass percentage of the polymer in the negative electrode sheet is 1%-3%, for example, 1.2%-2.8%, 1.5%-2.5%, 1.8%-2.2%, 2%-2.2%, etc. This can reduce the shedding of the negative electrode sheet, thereby improving the cycle performance of the battery containing the polymer.
[0191] In a fifth aspect, the present application provides a battery comprising the separator according to the third aspect and / or the electrode according to the fourth aspect, thereby providing the battery with excellent safety performance.
[0192] Typically, a battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0193] The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or solid.
[0194] In some embodiments of the present application, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0195] In some embodiments of the present application, when the battery is a lithium ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, or lithium tetrafluorooxalatophosphate.
[0196] In some embodiments of the present application, when the battery is a sodium ion battery, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate or sodium bis(trifluoromethylsulfonyl)imide.
[0197] In some embodiments of the present application, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone or diethyl sulfone.
[0198] In some embodiments of the present application, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0199] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0200] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0201] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0202] The present application has no particular limitation on the shape of the battery, which can be cylindrical, square, or any other shape. For example, FIG1 shows a square-structured battery 1 as an example.
[0203] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.
[0204] In some embodiments, batteries may be assembled into a battery module. The number of batteries contained in the battery module may be one or more. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.
[0205] Figure 3 shows an example battery module 2. Referring to Figure 3 , within the battery module 2, multiple batteries 1 may be arranged sequentially along the length of the battery module 2. Of course, any other arrangement is also possible. Furthermore, the multiple batteries 1 may be secured together using fasteners.
[0206] Optionally, the battery module 2 may further include a housing having a receiving space, and the plurality of batteries 1 are received in the receiving space.
[0207] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0208] Figures 4 and 5 illustrate an example battery pack 3. Referring to Figures 4 and 5 , the battery pack 3 may include a battery box and multiple battery modules 2 disposed within the battery box. The battery box comprises an upper case 31 and a lower case 32. The upper case 31 can be positioned over the lower case 32 to form an enclosed space for accommodating the battery modules 2. The multiple battery modules 2 can be arranged in any manner within the battery box.
[0209] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0210] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0211] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0212] Another example device may be a mobile phone, a tablet computer, a laptop computer, etc. Such a device is usually required to be light and thin, and may use a battery as a power source.
[0213] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0214] Preparation of the first polymer emulsion
[0215] Preparation Example A1
[0216] Weigh the first monomer (methyl acrylate), the second monomer (acrylic acid), and the third monomer (acrylamide) (mass ratio of first monomer / second monomer / third monomer: 90:5:5) and mix thoroughly. Add 1000g of the mixed monomers, 30g of sodium lauryl sulfate emulsifier, 10g of ammonium persulfate initiator, and 1200g of deionized water to a 5000mL four-necked flask equipped with a mechanical stirrer, thermometer, and condenser. Emulsify at high speed for 30 minutes. Under nitrogen, heat to 75°C and react for 4 hours. Then cool to below 40°C, adjust the pH to neutral, and filter the product. This yields the first polymer emulsion A1.
[0217] Preparation Examples A2 to A21, Preparation Examples A2-A21, based on Preparation Example A1, adjusted the monomer types and mass ratios to obtain the first polymer emulsions A2-A21, see Table 1 for details.
[0218] Table 1
[0219] A21: Weigh the first polymerizable monomer methyl acrylate, the second polymerizable monomer acrylic acid, the third polymerizable monomer acrylamide, and the fourth polymerizable monomer acrylonitrile (the mass ratio of the first polymerizable monomer, the second polymerizable monomer, the third polymerizable monomer, and the fourth polymerizable monomer is 70:10:10:10), and the rest is the same as the method for preparing A1.
[0220] Preparation of the second polymer emulsion
[0221] Preparation Example B1
[0222] Methyl acrylate (the first monomer), acrylamide (the third monomer), and acrylonitrile (the fourth monomer) were weighed and mixed in a mass ratio of 80:10:10. 200 g of the mixed monomers, 6 g of sodium lauryl sulfate (an emulsifier), 2 g of ammonium persulfate (an initiator), and 300 g of deionized water were added to a 1000 mL four-necked flask equipped with a mechanical stirrer, a thermometer, and a condenser. Emulsification was carried out at high speed for 30 minutes. Under nitrogen, the mixture was heated to 75°C and reacted for 4 hours. The mixture was then cooled to below 40°C, the pH adjusted to neutral, and filtered. This yielded the second polymer emulsion B1.
[0223] Preparation Example B2 to Preparation Example B20, Preparation Example B2-B20, adjusted the monomer types and mass ratios based on Preparation Example B1 to obtain the second polymer emulsion B2-B20, see Table 2 for details.
[0224] Table 2
[0225] Example 1
[0226] (1) Preparation of polymer
[0227] According to the weight percentage of the first polymer and the second polymer of 1:1, the first polymer emulsion A1 and the second polymer emulsion B2 were weighed, stirred and mixed evenly, and then spray-dried to obtain a polymer. The conditions of the spray-drying process were as follows: an inlet air temperature of 110°C, an outlet air temperature of 50°C, and an air pressure of 0.5 kPa to obtain a polymer.
[0228] (2) Preparation of isolation membrane
[0229] A commercially available PE microporous film with a thickness of 7 μm and an average pore size of 80 nm (from Zhuo Gao Electronic Technology Co., Ltd.) was used as the base film. The polymer prepared above was stirred and mixed uniformly in deionized water to obtain a slurry (solid content of 20%). The slurry was sprayed on both surfaces of the base film and dried to remove the solvent. The coating density of the coating composition on the substrate was 1.5 g / m 2 , and obtain an isolation film.
[0230] (3) Preparation of positive electrode sheet
[0231] Polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), conductive carbon black, and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 1.2:58.38:0.42:40 and stirred thoroughly to prepare a positive electrode slurry. 2 The loading amount is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet.
[0232] (4) Preparation of negative electrode sheet
[0233] Artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na) were added into deionized water in a mass ratio of 96.2:1.0:1.6:1.2, and stirred thoroughly to prepare a negative electrode slurry (solid content of 63%). 2 The loading amount is coated on the negative electrode current collector copper foil, and then dried, cold pressed and cut to obtain the negative electrode sheet.
[0234] (5) Preparation of electrolyte
[0235] At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then LiPF6 is dissolved in the above mixed solvent to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.
[0236] (6) Preparation of secondary batteries
[0237] The positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, wound, and cold-pressed (during which the separator is bonded to the electrode sheet) to obtain a battery cell; the battery cell is placed in an outer package, and the above-prepared electrolyte is added. After packaging, standing, formation, aging and other processes, a secondary battery is obtained.
[0238] The preparation methods of the lithium ion batteries of Examples 2 to 60 and Comparative Examples 1-14 are the same as those of the Examples, except that, based on Example 1, the types and mass ratios of the first polymer emulsion, the second polymer emulsion, the dispersant, and the butadiene polymer are adjusted to obtain the polymers of Comparative Examples 1-14 of Examples 2 to 60, as detailed in Table 3.
[0239] Table 3
[0240] The particle size and glass transition temperature of the polymers obtained in Examples 1-60 and Comparative Examples 1-14, as well as the cold pressing adhesion between the electrode and the separator in the obtained battery, the hardness of the battery cell, and the cycle performance of the battery were characterized. The characterization results are shown in Table 4.
[0241] Performance Testing
[0242] (1) Polymer particle size test
[0243] The analysis was performed using a laser particle size analyzer (Malvern 3000, MasterSizer 3000) using a helium-neon red light source as the primary light source. 1g of the sample to be tested was placed in a clean small beaker, along with 20ml of deionized water. Ultrasonication was performed at 53kHz / 120W for 5 minutes to ensure complete dispersion of the sample. The laser particle size analyzer was turned on, the optical system cleaned, and the background was automatically measured. The ultrasonicated sample solution was stirred to ensure uniform dispersion, then placed in the sample cell as required, and the particle size measurement was initiated. The measurement results were then read from the instrument.
[0244] (2) Glass transition temperature test
[0245] 6 ± 0.05 mg of sample was weighed into an Al crucible, shaken flat, and covered with a lid. The crucible was tested using a Netzsch DSC 3500 Sirius measuring instrument. The atmosphere was nitrogen, the purge gas rate was 50 mL / min, and the shielding gas rate was 100 mL / min. The heating conditions were: a heating rate of 10°C / min, and a temperature range of -70 to 200°C.
[0246] (3) Cold press bonding test steps
[0247] The negative electrode sheet and separator were stacked together and placed on a hot press. Pressing parameters were set at 25°C, 7t, and 15s to produce a bonded separator / negative electrode sheet sample. The separator / negative electrode sheet sample was cut into 150mm x 20mm rectangular strips. The electrode sheet side of the strip was affixed to a steel plate using double-sided tape. At one end of the strip, the separator and electrode sheet were separated by 2cm along the length to produce the test specimen.
[0248] The steel plate was held horizontally and secured with the lower clamp of a universal testing machine (Xie Qiang Instrument Manufacturing (Shanghai) Co., Ltd., Model CTM2100). The peeled end of the separator, as described above, was secured with the upper clamp of the universal testing machine and connected to a tensile testing machine. The test conditions were set to a tensile rate of 20 mm / min and a horizontal pull of 10 cm. Once the tensile force stabilized, the tensile force was recorded. The ratio of the tensile force to the sample width was used to determine the adhesion strength between the separator and the electrode.
[0249] (4) Battery cell hardness test steps
[0250] Place the resulting battery cell on a table with both ends level, with a 12cm wide hollowed-out area in the middle. Allow the cell to lie naturally flat and measure the deviation of the cell center from the horizontal baseline to assess its hardness. The greater the deviation of the cell center from the horizontal baseline, the lower the cell hardness.
[0251] (5) Battery cycle performance test steps
[0252] At 25°C, the prepared battery was charged at a constant current of 1 / 3C to 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C, left for 5 minutes, and then discharged at 1 / 3C to 2.5V. The obtained discharge capacity was recorded as the initial capacity C0. Repeat the above steps for the same battery and record the discharge capacity C of the battery after the nth cycle. n , then the battery capacity retention rate P after each cycle n =(C n / C0)×100%. The difference in cycle performance can be reflected by the battery capacity retention rate after 500 cycles.
[0253] Table 4
[0254] As can be seen from Table 4, the polymers of Examples 1-60 all have two glass transition temperatures, and the cold pressing adhesion between the separator and the negative electrode, the hardness of the battery cell, and the capacity retention rate of the battery are all higher than those of Comparative Examples 1-14. This shows that when the polymer of the present application is used for the separator, cold pressing adhesion between the separator and the electrode can be achieved, and the adhesion force is appropriate, thereby improving the cycle performance of the battery.
[0255] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.
[0256] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A polymer, wherein The invention comprises a first organic polymer and a second organic polymer, wherein the polymerized monomers of the first organic polymer include a first polymerized monomer, a second polymerized monomer and a third polymerized monomer, and the polymerized monomers of the second organic polymer include the first polymerized monomer, the third polymerized monomer and a fourth polymerized monomer, and the structure of the first polymerized monomer includes: Wherein, R1 includes a hydrogen atom or an alkyl group of 1 to 18 carbon atoms, and R2 includes an alkyl group of 1 to 18 carbon atoms. The structure of the second polymerizable monomer comprises: Wherein, R3 includes a hydrogen atom, a substituted or unsubstituted alkyl group of 1 to 18 carbon atoms; The structure of the third polymerizable monomer comprises: Wherein, R4 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 includes a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms; The structure of the fourth polymerizable monomer comprises: Here, R6 includes a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
2. The polymer according to claim 1, wherein The mass ratio of the first organic polymer to the second organic polymer is 1:(0.1-10), and can be optionally 1:(0.5-3).
3. The polymer according to claim 1 or 2, wherein In the polymerized monomers of the first organic polymer, the mass ratio of the first polymerized monomer, the second polymerized monomer and the third polymerized monomer is 1:0.05-0.5:0.05-0.5, and can be optionally 1:0.056-0.5:0.056-0.
5.
4. The polymer according to any one of claims 1 to 3, wherein In the polymerized monomers of the second organic polymer, the mass ratio of the first polymerized monomer, the third polymerized monomer and the fourth polymerized monomer is 1:0.05-0.5:0.05-0.5, and can be optionally 1:0.056-0.5:0.056-0.
5.
5. The polymer according to any one of claims 1 to 4, wherein The first polymerizable monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate or 2-hydroxypropyl methacrylate.
6. The polymer according to any one of claims 1 to 5, wherein The second polymerizable monomer includes at least one of acrylic acid, methacrylic acid, crotonic acid or heptonic acid.
7. The polymer according to any one of claims 1 to 6, wherein The third polymerizable monomer includes at least one of acrylamide, N-hydroxymethyl acrylamide or N-butoxymethyl acrylamide.
8. The polymer according to any one of claims 1 to 7, wherein The fourth polymerizable monomer includes at least one of acrylonitrile or methacrylonitrile.
9. The polymer according to any one of claims 1 to 8, wherein The invention also includes a dispersant, which includes at least one of sodium polystyrene sulfonate, sodium gluconate, sodium polyacrylate, sodium polymethacrylate, sodium polyphosphate, sodium lignin sulfonate or sodium polycarboxylate.
10. The polymer according to claim 9, wherein The number average molecular weight of the dispersant is 1000-100000, and can be optionally 5000-80000.
11. The polymer according to claim 9 or 10, wherein The mass ratio of the first organic polymer, the second organic polymer and the dispersant is 1:0.1-10:0.01-2, and can be optionally 1:0.5-3:0.05-1.
5.
12. The polymer according to any one of claims 1 to 11, wherein Butadiene polymers are also included.
13. The polymer according to claim 12, wherein The glass transition temperature of the butadiene polymer is less than or equal to 20°C, and can be optionally less than or equal to 15°C.
14. The polymer according to claim 12 or 13, wherein The volume average particle size Dv50 of the butadiene polymer is 100nm-300nm, and can be optionally 120nm-250nm.
15. The polymer according to any one of claims 12 to 14, wherein The viscosity of the butadiene polymer at 25° C. is 10 mPa·s to 300 mPa·s, and can be 80 mPa·s to 200 mPa·s.
16. The polymer according to any one of claims 12 to 15, wherein The butadiene polymer includes at least one of polybutadiene, styrene / butadiene copolymer or acrylonitrile / butadiene copolymer.
17. The polymer according to any one of claims 12 to 16, wherein The mass ratio of the first organic polymer, the second organic polymer and the butadiene polymer is 1:0.1-10:0.1-10, and can be optionally 1:0.5-3:0.5-8.
18. The polymer according to any one of claims 1 to 17, wherein The polymer has a first glass transition temperature less than or equal to 25°C and a second glass transition temperature greater than 25°C.
19. The polymer according to claim 18, wherein The first glass transition temperature is from -80°C to 25°C, and can be optionally from -60°C to 25°C.
20. The polymer according to claim 18 or 19, wherein The second glass transition temperature is 26°C to 100°C, and optionally 26°C to 90°C.
21. The polymer according to any one of claims 1 to 20, wherein The volume average particle size Dv50 of the polymer is 1 μm-15 μm, and can be 5 μm-10 μm; and / or, The number particle size distribution Dn10 of the polymer is 1 μm-5 μm, and can be optionally 1 μm-3 μm.
22. A method for preparing a polymer according to any one of claims 1 to 21, wherein include: blending water, an emulsifier, an initiator, a first organic monomer, a second polymerizable monomer, and a third polymerizable monomer to obtain a first polymer emulsion; blending water, an emulsifier, an initiator, a first polymerizable monomer, a third polymerizable monomer, and a fourth polymerizable monomer to obtain a second polymer emulsion; The first polymer emulsion and the second polymer emulsion are mixed to obtain a polymer.
23. The method according to claim 22, wherein: During the mixing of the first polymer emulsion and the second polymer emulsion, a dispersant and / or a butadiene polymer is also added.
24. A separation film, wherein: The invention comprises a polymer according to any one of claims 1 to 21 or a polymer prepared by the method according to claim 22 or 23.
25. A pole piece, wherein: The invention comprises a polymer according to any one of claims 1 to 21 or a polymer prepared by the method according to claim 22 or 23.
26. A battery, wherein: It comprises the isolation film as claimed in claim 24 and / or the pole piece as claimed in claim 25.
27. An electrical device, wherein: Comprising the battery of claim 26.